Studi Konflik Air Irigasi dan Alternatif Penyelesaiannya di Daerah Irigasi Kelingi Sumatera Selatan - Edward Saleh (Jurnal Keteknikan Pertanian, 2010)
Abstract Study of dispute management related to irrigation water use for agriculture and fishery at Kelingi irrigation area was conducted to determine the irrigation water management solution which is mutually beneficial between rice production and fish production of swift water pond. Kelingi Irrigation Area which is formerly planned for rice cultivation was built during the Dutch colonial era. Former water management pattern and its instruments were incapable to balance the rapid development found in the field which results in interest dispute among the water users. The study methods were consisted of PRA, interview by using questioner aids, and discussion/round table. Dispute management of irrigation water use for agriculture and fishery can be approached by using collaboration system in which all parties gain the advantage because this system is a truly and permanent solution. The recommendations from this study were as follows: 1) irrigation system improvement and increased service capability of the existing irrigation network, 2) balance planting pattern regulation and rice planting schedule as well as cultivation of fish and swift water pond fish at irrigation area level which was decided by using Decree Letter of Governor because this area was classified as district/city crossed irrigation, 3) farmers group empowerment and P3A/GP3A by related councils and institutions, 4) government provision for communication and collaboration between farmers and owner of swift water fish pond through justice and strict approaches in applying the existed regulations, 5) issuing of Local Irrigation Regulation at Province and District/City levels which consisted of swift water fish pond and irrigation water allotments, and 6) law enforcement in permit, supervision and action for every transgression by water users based on Local Regulation and the existed legislation.Keywords: irrigation water dispute, rice, swift water pondDiterima: 7 September 2009; Disetujui: 18 Januari 2010